2017
DOI: 10.1038/ismej.2017.189
|View full text |Cite
|
Sign up to set email alerts
|

The impact of elevated CO2 on Prochlorococcus and microbial interactions with ‘helper’ bacterium Alteromonas

Abstract: Prochlorococcus is a globally important marine cyanobacterium that lacks the gene catalase and relies on 'helper' bacteria such as Alteromonas to remove reactive oxygen species. Increasing atmospheric CO decreases the need for carbon concentrating mechanisms and photorespiration in phytoplankton, potentially altering their metabolism and microbial interactions even when carbon is not limiting growth. Here, Prochlorococcus (VOL4, MIT9312) was co-cultured with Alteromonas (strain EZ55) under ambient (400 p.p.m.)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
61
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 31 publications
5
61
0
1
Order By: Relevance
“…At the optimum temperature for growth, the dominant surface ecotypes of Prochlorococcus are able to survive exposures up to about 800 nM HOOH (Morris et al, 2011). And, during exposure to elevated CO 2 , Alteromonas strain EZ55 increases SOD expression and decreases catalase expression in co-cultures with Prochlorococcus (Hennon et al, 2017). And, during exposure to elevated CO 2 , Alteromonas strain EZ55 increases SOD expression and decreases catalase expression in co-cultures with Prochlorococcus (Hennon et al, 2017).…”
Section: Additional Factors That Impinge On the Helping Phenomenonmentioning
confidence: 99%
See 1 more Smart Citation
“…At the optimum temperature for growth, the dominant surface ecotypes of Prochlorococcus are able to survive exposures up to about 800 nM HOOH (Morris et al, 2011). And, during exposure to elevated CO 2 , Alteromonas strain EZ55 increases SOD expression and decreases catalase expression in co-cultures with Prochlorococcus (Hennon et al, 2017). And, during exposure to elevated CO 2 , Alteromonas strain EZ55 increases SOD expression and decreases catalase expression in co-cultures with Prochlorococcus (Hennon et al, 2017).…”
Section: Additional Factors That Impinge On the Helping Phenomenonmentioning
confidence: 99%
“…However, at lower or higher temperatures, their sensitivity to HOOH increases significantly, such that at 400 nM, they can only grow at or just below their temperature optimum (22-248C) (Ma et al, 2017). And, during exposure to elevated CO 2 , Alteromonas strain EZ55 increases SOD expression and decreases catalase expression in co-cultures with Prochlorococcus (Hennon et al, 2017). This indicates that ocean acidification may enhance HOOH production (via SOD) and diminish HOOH degradation (via catalase) by these helpers, a prospect supported by a measured sixfold decrease in the HOOH removal rates in the Alteromonas/Prochlorococcus co-cultures, relative to the unamended (present-day CO 2 ) controls.…”
Section: Additional Factors That Impinge On the Helping Phenomenonmentioning
confidence: 99%
“…While carbon availability is unlikely to limit photosynthetic rates in the open ocean, projected year 2100 CO 2 concentrations nevertheless stimulate growth rates in laboratory cultures of several important phytoplankton taxa (Feng et al , 2008, Fu et al , 2008, Hutchins et al , 2007, Lefebvre et al , 2012, Li et al , 2012, Sobrino et al , 2008, Spielmeyer & Pohnert, 2012, Sun et al , 2011, Tatters et al , 2013). Other experiments have shown phytoplankton growing slower at higher CO 2 (Iglesias-Rodriguez et al , 2008, Hoogstraten et al , 2012, Muller et al , 2012, Hennon et al , 2018), and in some cases different strains of the same species have opposite response to high CO 2 , even when tested side-by-side by a single researcher (Langer et al , 2009). These differential responses appear to have ecological consequences, as addition of CO 2 (and concomitant reduction of pH) to natural seawater communities induces substantial shifts in phytoplankton community composition (Tortell et al , 2002, Hare et al , 2007).…”
Section: Introductionmentioning
confidence: 96%
“…However, Prochlorococcus was the one exception to the rule of increased growth rate at high CO 2 amongst cyanobacteria (Fu et al , 2007a), and as a consequence the models of Dutkiewicz et al that considered both temperature increase and ocean acidification predicted that the competitive balance between these two groups would shift sufficiently over the coming century that Synechococcus would replace Prochlorococcus throughout its range, essentially leading to the worldwide elimination of Prochlorococcus ’ niche (Dutkiewicz et al, 2015). While this remarkable conclusion was based on a single published experiment with a single cultured strain of each genus (Fu et al, 2007a), subsequent experiments have confirmed that gene expression of the “helper” heterotrophic bacteria that it depends on to tolerate ubiquitous oxidative stress exposure (Morris et al , 2011, Hennon et al, 2018).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation